Performance and Cost Evaluation of Substituting Bambara Seed [Vigna subterranean (L) Verdc] Offal for Soyabean Meal in the Diets of Broiler Starter Chicks - Ekenyem, B.U.; Obih, T.K.O. (International Journal of Poultry Science, 2010)
A 28 day feeding trial was conducted using 160 marshal strain of day old broiler chicks fed 0, 5, 10 and 15% levels of Bambara Seed Offal (BSO) in a completely randomized design where BSO replaced soyabean meal weight for weight. Each of the four dietary treatments was further replicated four times. Routine vaccination and medication typical of broilers were strictly adhered to. The initial weight, final weight, weight gain, feed intake, feed conversion ratio, feed cost/kilogram and feed cost/kilogram weight gain were measured. Results show that birds on control (0% BSO) and T2 (5% BSO) with weight gains 584.78 and 583.48 respectively did not differ significantly (p>0.05) but were superior to those of levels 10% and 15% BSO (539.4 g and 505.0 g respectively). Both feed conversion ratio and feed cost/kg declined as the level of BSO increased from 0-15% while feed cost/kg weight gain did not maintain any particular trend. Treatment 2 (5% BSO) had the lowest cost of production feed wise. The control (0% BSO) and treatment 2 (5% BSO) were statistically similar (p>0.05) for final weight, weight gain, feed intake and feed conversion ratio.